How to pay for the war in times of imperfect commitment: Adam Smith and David Ricardo on the sinking fund. Issue 4 (3rd July 2016) - Signorino, Rodolfo
Abstract: The paper proposes a comparative analysis of Smith's and Ricardo's views on the sinking fund. It shows that Smith and Ricardo agreed in stressing the ineffectiveness of the sinking fund as a policy instrument targeted at public debt repayment and tax-burden relief, pointing out that its actual workings had paradoxically helped to increase rather than reduce British total debt-load. Moreover, their explanation of the sinking fund paradox integrates a defective fiscal commitment technology with powerful politicians' incentives to siphon off the money stored in the sinking fund to meet sudden increases of public expenditure whenever the occasion arose.